Gambling for dollars: Strategic hedge fund manager investment - Dan Bernhardt; Ed Nosal (Federal Reserve Bank of Chicago, 2013)
Hedge fund managers differ in ability and investors want to distinguish good ones from bad. Via the design of their investment strategies, better fund managers want to ease this inference problem while worse fund managers want to complicate it. We impose only the minimal restrictions on the nature the investment strategies that, on average, returns reflect the hedge fund manager's ability and that returns be bounded from below, and solve for the set of equilibria that emerge. We then show that under a variety of equilibrium refinements, a unique equilibrium obtains. In this equilibrium, investors set a cutoff standard for providing capital to a hedge fund: and invest if and only if returns exceed this cutoff. This induces less able hedge fund managers to adopt risky investment strategies that maximize the probability of meeting this cutoff by risking large losses if they fail. Over time, as investors learn about a hedge fund manager's ability and less able hedge fund managers are stochastically weeded out, investors set less demanding re-investment standards. Our economy reconciles many facts regarding hedge fund performance. For example, in a regression with fixed hedge fund manager effects, returns of more experienced hedge fund managers decline, even though the expected profits of investors rise with the hedge fund manager's experience; more experienced hedge funds deliver less volatile returns; persistence of returns is greater for better hedge funds; hedge fund failure rates are initially very high, but fall sharply with hedge fund manager experience; returns of exiting hedge funds are substantially worse than historical returns; and the longer is an investor's horizon, the lower is the expected return of the hedge funds in which he invests.
Keywords: G1; G23; 330; Financial institutions; financial markets; hedge funds; investments